Financial Constraints and Small and Medium Enterprises: A Review - Sasan Bakhtiari; Robert Breunig; Lisa Magnani; Jacquelyn Zhang (Institute of Labor Economics (IZA), 2020)
We review the literature on financial constraints and the performance of small and medium enterprises (SMEs). We consider the important role that SMEs play in the economies of Australia and the Organisation for Economic Cooperation and Development. We examine the role of financial constraints in SME growth, with emphasis on business cycles and credit access. We discuss issues that SMEs face in accessing financial resources for expansion. We look at the literature that evaluates the impact of financial constraints on key outcomes: employment, productivity and wages. We review key policy debates and consider where government involvement might be appropriate.
Keywords: D22; L25; 330; small and medium enterprises (SME); firm financial constraints; government business assistance; employment; wages; productivity; innovation